Pengelolaan Employee Relations pada Kementerian Agama Kabupaten Bogor - Matin, Aulia Muhamad; Astuti, Dyah Rahmi; Cholidah, Lida Imelda (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to find out the process of managing employee relations on the Ministry of Religion-Bogor Regency. This study was conducted using descriptive qualitative methods using primary and secondary data sources, and the data collection techniques used were observation, in-depth interviews, and documentation. The results of the study can be concluded the management of employee relations, by: 1) fact finding: employee data collection and surveys of employees; 2) planning and programming: determining goals, targets, and financial sources; 3) taking action and communicating: implementing programs, socializing, and using the interpersonal communication model; 4) evaluation: an annual report and evaluation as a measure of success.